2008
DOI: 10.1093/bfgp/eln039
|View full text |Cite
|
Sign up to set email alerts
|

The neurogenetic frontier--lessons from misbehaving zebrafish

Abstract: One of the central questions in neuroscience is how refined patterns of connectivity in the brain generate and monitor behavior. Genetic mutations can influence neural circuits by disrupting differentiation or maintenance of component neuronal cells or by altering functional patterns of nervous system connectivity. Mutagenesis screens therefore have the potential to reveal not only the molecular underpinnings of brain development and function, but to illuminate the cellular basis of behavior. Practical conside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
35
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 72 publications
(75 reference statements)
3
35
0
Order By: Relevance
“…It has previously been reported that larval raising conditions can have a direct effect on 628 sensitivity to auditory stimuli, with larvae raised at lower densities showing significantly 629 greater responsiveness (Burgess and Granato, 2008). In agreement with Burgess and…”
supporting
confidence: 81%
“…It has previously been reported that larval raising conditions can have a direct effect on 628 sensitivity to auditory stimuli, with larvae raised at lower densities showing significantly 629 greater responsiveness (Burgess and Granato, 2008). In agreement with Burgess and…”
supporting
confidence: 81%
“…S2). To quantify the degree of habituation for each individual tested, we calculated the ratio of the average SLC responsiveness during the last 10 habituation phase stimuli (i.e., stimuli [41][42][43][44][45][46][47][48][49][50] to the 10 prehabituation phase stimuli (i.e., stimuli [11][12][13][14][15][16][17][18][19][20]. The extent of habituation was similar in animals at 5, 10, and 14 dpf (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Despite the abundance of established habituation learning assays for adult rodent and zebrafish models, scaling these assays for systematic approaches is challenging given the inherent complexity and variability of adult behaviors, as well as the time required to train and test large numbers of animals (10)(11)(12)(13)(14)(15)(16). Larval zebrafish execute a repertoire of simple, well-defined, and stereotyped sensorimotor behaviors that have accessible and characterized circuitry and provide a vertebrate system amenable to large-scale forward genetic and chemical screening (17)(18)(19)(20)(21)(22)(23)(24). Although some studies have explored the capacity of zebrafish larvae for various forms of short-term learning and sensory conditioning, these assays have not been adapted to systematic approaches (25)(26)(27).…”
mentioning
confidence: 99%
“…9a). Zebrafish aggression levels can be affected by the environmental conditions during development (Marks et al, 2005), and behavioral assays are sensitive to changes in feeding regimen and diet, lighting conditions, pH, time of day, and experimental observer (Wahlsten et al, 2006;Burgess and Granato, 2008). Although we made an effort to maintain similar conditions between laboratories, we cannot rule out the contribution of one (or all) of these variables to the alterations in aggression levels.…”
Section: Discussionmentioning
confidence: 99%